2022
DOI: 10.3390/ijms23063147
|View full text |Cite
|
Sign up to set email alerts
|

Multicellular Modelling of Difficult-to-Treat Gastrointestinal Cancers: Current Possibilities and Challenges

Abstract: Cancers affecting the gastrointestinal system are highly prevalent and their incidence is still increasing. Among them, gastric and pancreatic cancers have a dismal prognosis (survival of 5–20%) and are defined as difficult-to-treat cancers. This reflects the urge for novel therapeutic targets and aims for personalised therapies. As a prerequisite for identifying targets and test therapeutic interventions, the development of well-established, translational and reliable preclinical research models is instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…The incorporation of research from various nations expands the viewpoint and enhances the applicability of the findings. The meta-analysis’s preponderance of HCC cases highlights the pressing need for efficient treatment options for this difficult-to-treat illness ( 26 , 27 ). The high percentage of patients with advanced-stage cancer emphasizes how crucial it is to investigate cutting-edge treatment options, like ICIs, in order to enhance patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of research from various nations expands the viewpoint and enhances the applicability of the findings. The meta-analysis’s preponderance of HCC cases highlights the pressing need for efficient treatment options for this difficult-to-treat illness ( 26 , 27 ). The high percentage of patients with advanced-stage cancer emphasizes how crucial it is to investigate cutting-edge treatment options, like ICIs, in order to enhance patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that patient-derived xenograft models exhibit a higher fidelity to the clinical response to therapy compared to conventional xenograft models. 23 In vitro cell lines and mouse allografts are inadequate for meeting the preclinical needs. 19 Furthermore, the utilization of humanized patient-derived xenograft models presents a highly effective platform for the examination of the intricate interactions occurring between the immune system and the microbiome.…”
Section: Patient-derived Xenograftsmentioning
confidence: 99%
“…Among gastrointestinal tumors, the survival rate of gastric and pancreatic cancers is 5%−20%, most GCs are diagnosed in the late stage because there are no obvious symptoms in the early stage, leading to a high mortality rate. [234][235][236][237][238] Epigenetic changes are valuable biomarkers for GC prognosis. Jang et al found that the trimethylated state of H3K9 is highly expressed and positively correlated with tumor staging.…”
Section: Gastric Cancer (Gc)mentioning
confidence: 99%
“…Among gastrointestinal tumors, the survival rate of gastric and pancreatic cancers is 5%−20%, most GCs are diagnosed in the late stage because there are no obvious symptoms in the early stage, leading to a high mortality rate. 234 , 235 , 236 , 237 , 238 Epigenetic changes are valuable biomarkers for GC prognosis. Jang et al.…”
Section: Abnormal Expression Of Histone‐modifying Enzymes and Human C...mentioning
confidence: 99%